The small pelagic fish food landscape and its use by common terns Sterna hirundo in the Wadden Sea - Margot A. M. Maathuis; Petra Manche; Bram Couperus; Bram Parmentier; Jan Jaap Poos; Martin Poot; Hans Schekkerman; Serdar Sakinan; Ingrid Tulp (Marine Biology, 2025)
Small pelagic fish (SPF) play a vital role in marine ecosystems, transferring energy from plankton to higher trophic levels. However, SPF dynamics in shallow coastal areas are often under-studied, despite their importance as crucial prey near breeding sites of fish-eating birds such as common terns ( Sterna hirundo ). This study had two connected objectives: to map the pelagic fish food landscape in the inlets of the Dutch Wadden Sea and to describe its use by common terns. Two hydro-acoustic fish surveys were conducted in May and October 2022, while tern distribution was assessed using aerial counts and GPS tracking. Prey selection was analyzed through camera traps and DNA analysis of faeces. Herring and sprat were the predominant species in the SPF community, with sandeel also abundant in May. Smelt was most common in freshwater-influenced areas. Most fish were below 12 cm, fitting the preferred size range for common terns. SPF energy density ranged from 20.1 to 22.1 kJ/g dry weight, with sprat having the highest values. SPF biomass showed significant spatiotemporal variability across transects, inlets, and seasons. Common terns foraged frequently around the gullies, feeding mostly on herring. A significant correlation was found between fish biomass and common tern density, indicating food landscape may be a good predictor of tern distribution and vice versa. This study presents the first integrated biomass estimates of SPF in the subtidal areas of Dutch Wadden Sea for both spring and autumn, providing essential data for future energy budget models and management strategies.

Migratory Birds Advance Spring Arrival and Egg‐Laying in the Arctic, Mostly by Travelling Faster - Thomas K. Lameris; Michiel P. Boom; Rascha J. M. Nuijten; Nelleke H. Buitendijk; Götz Eichhorn; Bruno J. Ens; Klaus‐Michael Exo; Petr M. Glazov; Sveinn Are Hanssen; Philip Hunke; Henk P. van der Jeugd; Margje E. de Jong; et al. (Global Change Biology, 2025)
In the current warming climate, many organisms in seasonal environments advance their timing of reproduction to benefit from resource peaks earlier in spring. For migrants, the potential to advance reproduction may be constrained by their migration strategies, notably their ability to advance arrival at the breeding grounds. Recent studies show various changes in migration strategies, including wintering closer to the breeding grounds, earlier departure from the wintering grounds or faster travels by spending less time at stopover sites. However, whether such changes lead to earlier arrival or earlier breeding remains an open question. We studied changes in migration and reproduction timing in 12 populations of nine migratory birds, including seabirds, shorebirds, birds of prey and waterfowl breeding at Arctic sites bordering the Greenland and Barents Sea, a region undergoing rapid climate warming. The timing of migration and reproduction was derived from tracking and field data and analysed to study (1) how timing has changed in response to the changing moment of snowmelt at the breeding grounds and (2) what adjustments in migration strategies this involved. We found that in years with early snowmelt, egg‐laying in multiple populations advanced, but only two waterfowl populations also advanced arrival in the Arctic. In contrast, arrival in the Arctic generally advanced with time, even when snowmelt or egg‐laying dates did not advance. Earlier arrival with time was mostly explained by populations traveling to the Arctic faster, likely spending less time at stopover sites. Inability to forecast conditions in the Arctic may limit birds to adjust migration timing to annually varying snowmelt, but we show that several species, particularly waterfowl, are able to travel faster and advance the timing of migration over the years. The question remains whether this reflects adaptations to Arctic climate change or other factors, for example, environmental changes along the migratory route.

Mismatch‐induced growth reductions in a clade of Arctic‐breeding shorebirds are rarely mitigated by increasing temperatures - Thomas K. Lameris; Pavel S. Tomkovich; James A. Johnson; R. I. Guy Morrison; Ingrid Tulp; Simeon Lisovski; Lucas DeCicco; Maksim Dementyev; Robert E. Gill; Job ten Horn; Theunis Piersma; Zachary Pohlen; et al. (Global Change Biology, 2022)
In seasonal environments subject to climate change, organisms typically show phenological changes. As these changes are usually stronger in organisms at lower trophic levels than those at higher trophic levels, mismatches between consumers and their prey may occur during the consumers’ reproduction period. While in some species a trophic mismatch induces reductions in offspring growth, this is not always the case. This variation may be caused by the relative strength of the mismatch, or by mitigating factors like increased temperature‐reducing energetic costs. We investigated the response of chick growth rate to arthropod abundance and temperature for six populations of ecologically similar shorebirds breeding in the Arctic and sub‐Arctic (four subspecies of Red Knot Calidris canutus , Great Knot C . tenuirostris and Surfbird C . virgata ). In general, chicks experienced growth benefits (measured as a condition index) when hatching before the seasonal peak in arthropod abundance, and growth reductions when hatching after the peak. The moment in the season at which growth reductions occurred varied between populations, likely depending on whether food was limiting growth before or after the peak. Higher temperatures led to faster growth on average, but could only compensate for increasing trophic mismatch for the population experiencing the coldest conditions. We did not find changes in the timing of peaks in arthropod availability across the study years, possibly because our series of observations was relatively short; timing of hatching displayed no change over the years either. Our results suggest that a trend in trophic mismatches may not yet be evident; however, we show Arctic‐breeding shorebirds to be vulnerable to this phenomenon and vulnerability to depend on seasonal prey dynamics.

Responses of wintering geese to the designation of goose foraging areas in The Netherlands - Kees Koffijberg; Hans Schekkerman; Henk van der Jeugd; Menno Hornman; Erik van Winden (Ambio, 2017)

Reproductive timing and investment in relation to spring warming and advancing agricultural schedules - Julia Schroeder; Theunis Piersma; Niko M. Groen; Jos C. E. W. Hooijmeijer; Rosemarie Kentie; Pedro M. Lourenço; Hans Schekkerman; Christiaan Both (Journal of Ornithology, 2012)

Long-term trends in survival of a declining population: the case of the little owl (Athene noctua) in the Netherlands - Pascaline J. Le Gouar; Hans Schekkerman; Henk P. van der Jeugd; Arjan Boele; Ronald van Harxen; Piet Fuchs; Pascal Stroeken; Arie J. van Noordwijk (Oecologia, 2011)

Body condition of shorebirds upon arrival at their Siberian breeding grounds - Ingrid Tulp; Hans Schekkerman; Raymond H. G. Klaassen; Bruno J. Ens; G. Henk Visser (Polar Biology, 2009)

Mortality of Black-tailed Godwit Limosa limosa and Northern Lapwing Vanellus vanellus chicks in wet grasslands: influence of predation and agriculture - Hans Schekkerman; Wolf Teunissen; Ernst Oosterveld (Journal of Ornithology, 2009)

Phylogeography of the Black-tailed Godwit Limosa limosa: substructuring revealed by mtDNA control region sequences - Jacob Höglund; Tomas Johansson; Albert Beintema; Hans Schekkerman (Journal of Ornithology, 2009)

Mechanisms promoting higher growth rate in arctic than in temperate shorebirds - Hans Schekkerman; Ingrid Tulp; Theunis Piersma; G. Henk Visser (Oecologia, 2003)